The Comparison of Sensitivity and Specificity of ELISA-based Microneutralization Test with Hemagglutination Inhibition Test to Evaluate Neutralizing Antibody against Influenza Virus (H1N1) - Ahmad TAVAKOLI; Farhad REZAEI; Gazal Sadat FATEMI NASAB; Fatemeh ADJAMINEZHAD-FARD; Zahra NOROOZBABAEI; Talat MOKHTARI-AZAD (Tehran University of Medical Sciences, 2017)
Background: The most common serological assay to measure anti-influenza antibodies is hemagglutination inhibition (HI) assay. Recently, neutralizing antibodies against influenza virus infection or vaccination can also be detected using microneutralization assays and occasionally, have greater sensitivity than the standard HI assays. The study aimed to compare the sensitivity and specificity of ELISA-based microneutralization (microNT-ELISA) and conventional HI assays in order to detect influenza H1N1 virus antibodies. Methods: MicroNT-ELISA was set up according to the WHO Manual on Influenza Diagnosis and Surveillance in Virology Department of Tehran University of Medical Sciences for the detection of neutralizing antibodies against H1N1 influenza virus in 2013. Fifty serum samples were analyzed with both HI and microNT-ELISA assays. Correlation between methods was calculated by linear regression analysis. Results: The linear correlation coefficient squares, R2, of microNT-ELISA and HI test was 0.61 (P<0.0001) and we observed a high index of coincidence between the two tests. According to McNemar's test, there was no statistically significant difference between these two assays (P>0.05). Conclusion: The sensitivity and specificity of microNT-ELISA assay were high (87% and 73%, respectively) and closely related to gold standard test results. Therefore, microNT-ELISA is recommended as an alternative or complementary test to conventional HI assay for serological and epidemiological purposes.